A Combination of Intrathecal and Intramuscular Application of Human Mesenchymal Stem Cells Partly Reduces the Activation of Necroptosis in the Spinal Cord of SOD1G93A Rats - Řehořová, Monika; Vargová, Ingrid; Forostyak, Serhiy; Vacková, Irena; Turnovcová, Karolína; Kupcová Skalníková, Helena; Vodička, Petr; Kubinová, Šárka; Syková, Eva; Jendelová, Pavla (Stem cells translational medicine, 2019)
An increasing number of studies have demonstrated the beneficial effects of human mesenchymal stem cells (hMSC) in the treatment of amyotrophic lateral sclerosis (ALS). We compared the effect of repeated intrathecal applications of hMSC or their conditioned medium (CondM) using lumbar puncture or injection into the muscle (quadriceps femoris), or a combination of both applications in symptomatic SOD1G93A rats. We further assessed the effect of the treatment on three major cell death pathways (necroptosis, apoptosis, and autophagy) in the spinal cord tissue. All the animals were behaviorally tested (grip strength test, Basso Beattie Bresnahan (BBB) test, and rotarod), and the tissue was analyzed immunohistochemically, by qPCR and Western blot. All symptomatic SOD1 rats treated with hMSC had a significantly increased lifespan, improved motor activity and reduced number of Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) positive cells. Moreover, a combined hMSC delivery increased motor neuron survival, maintained neuromuscular junctions in quadriceps femoris and substantially reduced the levels of proteins involved in necroptosis (Rip1, mixed lineage kinase-like protein, cl-casp8), apoptosis (cl-casp 9) and autophagy (beclin 1). Furthermore, astrogliosis and elevated levels of Connexin 43 were decreased after combined hMSC treatment. The repeated application of CondM, or intramuscular injections alone, improved motor activity; however, this improvement was not supported by changes at the molecular level. Our results provide new evidence that a combination of repeated intrathecal and intramuscular hMSC applications protects motor neurons and neuromuscular junctions, not only through a reduction of apoptosis and autophagy but also through the necroptosis pathway, which is significantly involved in cell death in rodent SOD1G93A model of ALS. Stem Cells Translational Medicine 2019;8:535-547.
Keywords: Motor Neurons; modely nemocí na zvířatech; potkani transgenní; protein-serin-threoninkinasy; Longevity; Injections, Intramuscular; beclin 1; nekroptóza; potkani Sprague-Dawley; Spinal Cord; dlouhověkost; superoxiddismutasa 1; injekce intramuskulární; Protein Serine-Threonine Kinases; serin-threoninkinasy interagující s receptory; Beclin-1; Injections, Spinal; kaspasa 9; Mesenchymal Stem Cell Transplantation; Quadriceps Muscle; Amyotrophic lateral sclerosis; čtyřhlavý sval stehenní; Necroptosis; spinální injekce; Rats, Transgenic; krysa rodu Rattus; Amyotrophic Lateral Sclerosis; Superoxide Dismutase-1; Animals; Autophagy; lidé; Caspase 9; mícha; Humans; zvířata; Rats; Disease Models, Animal; motorické neurony; Receptor-Interacting Protein Serine-Threonine Kinases; transplantace mezenchymálních kmenových buněk; Mesenchymal stem cells; Mesenchymal Stem Cells; amyotrofická laterální skleróza; Apoptosis; Rats, Sprague-Dawley; mezenchymální kmenové buňky